2018
DOI: 10.1503/cmaj.180463
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations on screening for breast cancer in women aged 40–74 years who are not at increased risk for breast cancer

Abstract: KEY POINTS• Low-certainty evidence indicates that screening for breast cancer with mammography results in a modest reduction in breast cancer mortality for women aged 40 to 74 years; the absolute benefit is lowest for women younger than 50 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
145
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(186 citation statements)
references
References 75 publications
1
145
0
16
Order By: Relevance
“…Young age at diagnosis is generally defined as a diagnosis before age 40 [2,7], but can be stratified by other ages. Current Canadian screening guidelines do not recommend screening for breast cancer until age 50, unless the patient is at increased risk for breast cancer [8]. Young age at diagnosis is linked to later stage of tumour progression at diagnosis, and worse clinical outcomes [2,7,[9][10][11][12][13][14].…”
Section: Young-onset Breast Cancermentioning
confidence: 99%
“…Young age at diagnosis is generally defined as a diagnosis before age 40 [2,7], but can be stratified by other ages. Current Canadian screening guidelines do not recommend screening for breast cancer until age 50, unless the patient is at increased risk for breast cancer [8]. Young age at diagnosis is linked to later stage of tumour progression at diagnosis, and worse clinical outcomes [2,7,[9][10][11][12][13][14].…”
Section: Young-onset Breast Cancermentioning
confidence: 99%
“…Care's 2018 recommendations on mammography screening for women at average risk recommends that women aged 50-74 years be screened every 2-3 years. 1 Women at average risk are defined as those without a personal or family history of breast cancer who are not (and whose first-degree relatives are not) carriers of specific gene mutations (e.g., BRAC1, BRAC2) and who did not have chest radiation before age 30 years or in the previous 8 years. Unlike previous recommendations, the new recommendation is now "conditional on the relative value that a woman places on the possible benefits and harms from screening," which suggests that there is no "right" decision; rather, decisions should fit with women's values and preferences.…”
Section: T He Canadian Task Force On Preventive Healthmentioning
confidence: 99%
“…Unlike previous recommendations, the new recommendation is now "conditional on the relative value that a woman places on the possible benefits and harms from screening," which suggests that there is no "right" decision; rather, decisions should fit with women's values and preferences. 1 To make informed decisions about mammography that align with their values and preferences, women need sufficient information about risks, benefits and available alternatives. 2 Educational materials are one tool to share this information.…”
Section: T He Canadian Task Force On Preventive Healthmentioning
confidence: 99%
“…10 It is critical that clinical guidance is based on systematic review of evidence that uses accepted methods to minimize bias and considers the totality of evidence, 11 which the task force did in developing its recommendations on breast cancer screening. 12 Third, Dr. Yaffe suggested that observational data on breast cancer screening make a clear and strong case that benefits outweigh the harms. In 2016, the United States Preventive Services Task Force did a systematic review of the types of observational studies on breast cancer screening that Dr. Yaffe used to provide evidence that supported his position.…”
mentioning
confidence: 99%